Syngas Production from CO2 Reforming of Methane over Neodymium Sesquioxide Supported Cobalt Catalyst - Ayodele, Bamidele V.; Hossain, Sk Safdar; Lam, Su Shiung; Osazuwa, Osarieme U.; Khan, Maksudur R.; Cheng, C. K. (Elsevier Ltd, 2016)
This paper reports for the first time the catalytic dry (CO2) reforming of methane over 20 wt%Co/80 wt%Nd2O3catalyst. The catalyst was synthesized by wet-impregnation procedure and its physicochemical properties were characterized by TGA, XRD, FESEM, EDX, FTIR, H2-TPR and TPD followed by activity testing in afixed-bed reactor. The effects of feed ratios (CH4:CO2) ranged 0.1-1.0, reactant (CH4and CO2) partial pressure (0-50 kPa) and temperature ranged 923 to 1023 K on the activity of the catalyst were investigated. The conversion of both reactants increased with the feed ratio and reaction temperature reaching maximum values of 62.7% and 82% for CH4 and CO2, respectively. The CO2 reforming of methane resulted into the formation of syngas with maximum yields of 59.91% and 62.02% for H2 and CO, respectively, leading to formation of syngas ratio of 0.97. The mechanistic proposition includes the CH4 and CO2 adsorption, activation of CH4 by methane cracking and gasification of carbon deposited on the catalyst surface. The experimental data were fitted by Langmuir Hinshelwood kinetic models. Activation energy values of 21.89 and 62.04 kJ mol-1 were obtained for the consumption of CO2 and CH4 respectively from Langmuir-Hinshelwood models. The lower values of activation energy obtained for CO2 compared to that of CH4 shows that the rate of consumption of CO2 was faster than that of CH4 leading to higher conversion of CO2.